Dos jogos concretos aos jogos eletrônicos intervenções pedagógicas e construção das relações espaciais - Gonçalves, Érica de Cássia (Editora Oficina Universitária, 2022)
This work comes from a scientific research that, when transformed into a book, "increases the possibility of contributing to the continuing education of professionals in Education, Psychology and Psychopedagogy, in addition to indicating to electronic game developers the need to adapt them to the specific characteristics of educational and psychopedagogical processes, expanding the possibilities of actions to be performed by the player and, thus, increasing their influence on cognitive development, active learning and the achievement of autonomy in children and adolescents". LIA LEME ZAIA